Pengaruh Pajak Daerah dan Retribusi Daerah Terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Bogor (2020-2025) - Putri Nuna Maftuha; Zakie Hanifan; Yudiana . (CV. ITTC INDONESIA, 2026)
Regional Original Revenue (PAD) is an important indicator that reflects a region's fiscal independence in financing governmental administration and regional development. Local taxes and regional retributions are the main components of PAD that contribute significantly to strengthening local fiscal capacity. Bogor Regency possesses substantial economic potential; however, fluctuations in PAD realization during the 2020–2025 period indicate the need to examine the contribution of local taxes and regional retributions to regional revenue. This study aims to analyze the effect of local taxes on Regional Original Revenue (PAD), the effect of regional retributions on PAD, and the simultaneous effect of local taxes and regional retributions on PAD in Bogor Regency during the period 2020–2025. This research employed a quantitative approach using descriptive and verificative methods. The population consisted of all realization data of local taxes, regional retributions, and Regional Original Revenue of Bogor Regency. The sample comprised realization data of local tax revenue, regional retribution revenue, and PAD from 2020 to 2025, selected using purposive sampling techniques. Secondary data were obtained from the Regional Budget Realization Reports (APBD) published by the Regional Revenue Management Agency (BAPPENDA) of Bogor Regency. Data collection was conducted through documentation studies. Data analysis was performed using multiple linear regression with SPSS version 27, including descriptive analysis, classical assumption tests, partial tests (t-test), simultaneous tests (F-test), and coefficient of determination (R²). The findings indicate that local taxes have a positive and significant effect on PAD, with a significance value of 0.003 (< 0.05). Conversely, regional retributions do not have a significant effect on PAD, with a significance value of 0.826 (> 0.05). Simultaneously, local taxes and regional retributions significantly affect PAD, with a significance value of 0.001 (< 0.05). Furthermore, the adjusted coefficient of determination (Adjusted R Square) of 0.983 indicates that 98.3% of the variation in PAD can be explained by local taxes and regional retributions. This study concludes that local taxes are the dominant factor influencing the increase in PAD in Bogor Regency, while regional retributions have not yet made a significant partial contribution. Therefore, local governments should optimize local tax management and improve the effectiveness of regional retribution collection to strengthen fiscal independence and support sustainable regional development.